2016
DOI: 10.1136/bcr-2016-216473
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus parainfluenzaeendocarditis with systemic embolisation following maxillary sinusitis

Abstract: The authors present a case of a man with Haemophilus parainfluenzae endocarditis complicated with embolisation to the central nervous system. The patient had no evidence of endocarditis by transoesophageal and transthoracic echocardiograms at baseline, but shortly after developed large mitral valve vegetations with valve rupture. The case highlights how rapidly structural valve damage can ensue despite good clinical and laboratorial antibiotic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…3,8 Our patient did not complain of any oropharyngeal or upper respiratory tract symptoms; however, he was found by CT scan to have maxillary sinusitis, which has been associated with the development of H parainfluenzae endocarditis with cerebral emboli. 10 Additionally, our case exhibited several relatively unique features. First, it is quite rare for endocarditis to present with headache as the primary complaint, a symptom that may have been related to the dissemination of septic emboli into meningeal vessels.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…3,8 Our patient did not complain of any oropharyngeal or upper respiratory tract symptoms; however, he was found by CT scan to have maxillary sinusitis, which has been associated with the development of H parainfluenzae endocarditis with cerebral emboli. 10 Additionally, our case exhibited several relatively unique features. First, it is quite rare for endocarditis to present with headache as the primary complaint, a symptom that may have been related to the dissemination of septic emboli into meningeal vessels.…”
Section: Discussionmentioning
confidence: 75%
“…These results are similar to the case described by Barreto et al, in which the TTE was normal and the TEE showed significant valvular perforation with vegetation. 10 This illustrates the value of obtaining a TEE to assess for complications that may not be apparent on TTE. 11 Furthermore, the severity of thrombocytopenia was another interesting aspect of the patient's clinical presentation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation